2013
DOI: 10.1002/esp.3449
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of secondary minerals in crusts developed on sandstone exposures

Abstract: Previous research on rock weathering crusts has revealed their large variability depending on the type of host rocks and development of weathering processes. The composition of crusts developed on natural sandstone exposures is less documented in the literature in comparison to those developed on architectonic stones. In both cases, previous research has focused mainly on the progress of salt weathering. This study considers the surfaces of sandstone tors in the Polish Outer Carpathians. The exposed parts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Granular aggregates of glauconite occur as a minor admixture. Spherical microaggregates of pyrite framboids and/or their alteration products were sometimes observed [38,52]. The average porosity of the Ciężkowice sandstones from the Stone Town tors is 6.78% [52], reaching 12.0% in the weathered varieties [38].…”
Section: The Ciężkowice Sandstones and Their Efflorescencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Granular aggregates of glauconite occur as a minor admixture. Spherical microaggregates of pyrite framboids and/or their alteration products were sometimes observed [38,52]. The average porosity of the Ciężkowice sandstones from the Stone Town tors is 6.78% [52], reaching 12.0% in the weathered varieties [38].…”
Section: The Ciężkowice Sandstones and Their Efflorescencesmentioning
confidence: 99%
“…The weathered surface of the sandstone tors is covered in places by hard crusts composed mainly of iron minerals (among others hematite Fe 2 O 3 and goethite FeOOH) and various salts that may also occur in the form of very thin layers as subflorescences beneath the surface [52,53] [30,52,54,55]. The efflorescences sometimes cover wider surfaces of the tors, as their crystallization and preservation depend on the atmospheric conditions and rock exposition.…”
Section: The Ciężkowice Sandstones and Their Efflorescencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural protective layer, irregularly covering the surfaces of Carpathian tors, consists of a hard weathering crust, usually 1-2 cm thick, and -more rarely -several centimetres thick (Alexandrowicz and Pawlikowski, 1982;Rzepa et al, 2011;Alexandrowicz et al, 2012Alexandrowicz et al, , 2014Marszałek et al, 2012). It is composed of very thin laminae, macroscopically differing in colour, running either as a continual or broken layer, in parallel to the rock surface.…”
Section: Rock Thermo-humidity and Their Implications For Weatheringmentioning
confidence: 99%
“…In natural conditions, it enables the successive regeneration of damaged surfaces by developing a new protective crust. The weathering crust and co-existing weathering micro-forms are at a different stage of development, thus testifying to the continuity and progress of the process of transformation of the rock surface (e.g., Robinson and Williams, 1994;Cílek, 1997;Turkington and Paradise, 2005;Mikuláš, 2007b;Robinson, 2007;Alexandrowicz et al, 2014). The measurements demonstrated that the particular height-zones of the tors showed differences in the thermo-humidity regime of the exposed surfaces (Alexandrowicz and Brzeźniak, 1989).…”
Section: Rock Thermo-humidity and Their Implications For Weatheringmentioning
confidence: 99%